U-Pb ages of the Nardanda Pegmatite of the Kathmandu Crystalline Nappe and augen gneisses of the Gosaikund Crystalline Nappe, Central Nepal Himalaya (Journal of Nepal Geological Society, 2011)
Available with full text.